Bank-Specific Factors as Determinants of Dividend Yield: Case of the Indonesia Stock Exchange - Mai, Muhamad Umar (Universitas Syiah Kuala, 2020)
Objective The purpose of this study is to observe the impact on dividend yields caused by bank-specific factors of profitability, liquidity, bank size, leverage, and bank growth.Design/methodology This study was conducted on the bank sub-sector of the Indonesia Stock Exchange for the period of 2009-2018, which resulted in 367 bank-year observations. The sample is determined using a purposive sampling method with a criteria of bank that paid dividends hence resulting in 134 bank-year observations. However, to achieve the fit model's goodness, the final sample used was 120 bank-year observations. This paper used OLS Multiple Linear Regression for analyzing data.Results The results show that return on assets and leverage negatively affects dividend yield, and bank size has a positive effect. Meanwhile, growth and liquidity do not affect dividend yield. These results are useful for investors in determining their investment decisions in the banks shares on the Indonesia Stock Exchange and for managers in considering bank-specific factors to meet investors' preferences for dividends.